The Capital Gaps between Female and Male Entrepreneurs - Bracha Efroni (Institute of Economic Research (IER), 2017)
Research background: Today countries have realized the importance ofsmall and medium enterprises (SMEs) to economic and social development. Entrepreneurship currently provides the most critical source of economic growth for countries. In most countries women own about 30% of small businesses. Since small businesses are the pillar of the economy, entrepreneurship is its growth engine, and women constitute about 50% of the population, it is important to research businesses and entrepreneurship among women so as to strengthen the economy. Women who decide to engage in entrepreneurship encounter many challenges, during both the establishment and management of the venture. Some of these challenges are shared by both male and female entrepreneurs, while some are relevant only to women. Purpose of the article: Since female entrepreneurship is extremely vital to a country's economy, entrepreneurship among women must be encouraged. To do this, it is first necessary to understand the gaps between male and female entrepreneurs. Such gaps can only be reduced bycontinuing to research their origin and how they can be decreased. Methodology/methods: This article is based on literary research focusing on the differences between male and female entrepreneurship. Nearly one hundred articles, reports, and books were reviewed. The study results were synthesized on the basis of 40 works. Findings & Value added: Three main types of entrepreneurial gaps were found between women and men: social capital, financing capital, and human capital. The gender gap in entrepreneurship is explained in women's structural disadvantages regarding the achievement of the resources relevant to the success of the business.
Keywords: L26; J16; 330; female entrepreneurship; gender gap; human capital; financing capital; social capital